Proteoglycan-4 predicts good prognosis in patients with hepatocellular carcinoma receiving transcatheter arterial chemoembolization and inhibits cancer cell migration in vitro - Guo, Yuan; Hu, Hong Tao; Xu, Shi Jun; Xia, Wei Li; Zhao, Yan; Zhao, Xiao Hui; Zhu, Wen Bo; Li, Fang Ting; Li, Hai Liang (Frontiers in Oncology, 2022)
Purpose To search for adaptive response molecules that affect the efficacy of transcatheter arterial chemoembolization (TACE), analyze their clinical correlation with and prognostic value for hepatocellular carcinoma (HCC), and explore their impact on cell biological behavior and their mechanisms of action. Methods HCC tissue gene sequencing was used to identify differentially expressed genes. The expression of proteoglycan 4 (PRG4) in the serum of 117 patients with HCC who received TACE was detected by enzyme-linked immunosorbent assay. Serum-free medium mimicked TACE-induced nutrient deprivation. Cells with stable knockdown of PRG4 (shPRG4) were constructed to verify the effect and mechanism of PRG4 on the biological behavior of HCC cells in vitro. Results The expression of PRG4 was significantly elevated under TACE-induced starvation conditions. Low PRG4 expression was associated with worse response to TACE treatment, shorter survival time, and stronger HCC migration ability. Furthermore, in vitro experiments showed that knockdown of PRG4 promoted HCC cell migration by enhancing epithelial–mesenchymal transition (EMT) while did not affect proliferation. When PRG4 expression was low, starvation treatment impaired the migratory ability of HCC cells and reduced the chemosensitivity of HCC cells to epirubicin. Conclusions PRG4 expression predicts survival and TACE treatment response in patients with HCC. Furthermore, knockdown of PRG4 enhanced EMT, leading to HCC cell migration. PRG4 may serve as a biomarker for HCC patients receiving TACE.